Pengaruh Reward dan Pengakuan Kerja terhadap Motivasi Kerja pada Karyawan Dealer Honda Daerah Meulaboh Kabupaten Aceh Barat - Siti Nurmuslima; Ivon Jalil; Mardaleta Mardaleta (Indo Publishing, 2026)
This study aims to examine and analyze the partial and simultaneous effects of reward and work recognition on employee work motivation at Honda Dealerships in Meulaboh, West Aceh Regency (CV Valen Motor and PT Kurniaputra Mandiri). This research employs a quantitative approach utilizing a total sampling technique (census) involving 50 employee respondents, where primary data were collected through questionnaires and analyzed using multiple linear regression and hypothesis testing via IBM SPSS. The partial test results (t-test) indicate that the reward variable (X1) has a positive and significant effect on work motivation (Y) with a significance value of 0.002 < 0.05, whereas the work recognition variable (X2) has no significant effect with a significance value of 0.364 > 0.05. Simultaneously (F-test), both independent variables significantly affect employee work motivation with a significance value of 0.006 < 0.05 and yield an Adjusted R Square value of 15.9%, implying that the remaining 84.1% is influenced by other factors outside this research model. Based on these findings, it is recommended that the company management continuously develop an objective, fair, transparent, and performance-oriented reward system to maintain and enhance employee work motivation sustainably.